Comparison of Different 3D Surface Registration-Based Methods to Assess Facial Asymmetry - Annalisa Cappella; Riccardo Solazzo; Luisa Gigante; Alice Gervasoni; Daniele Maria Gibelli; Claudia Dolci; Gianluca Martino Tartaglia; Chiarella Sforza (Diagnostics)
Background/Objectives: Facial asymmetry is gaining an increasing diagnostic interest in many clinical contexts. Several three-dimensional surface-based methods have been proposed for its assessment; however, they might provide non-equivalent data. Since there is a lack of comparative studies in these terms, this study aims to compare three methods for assessing the asymmetry of the face and facial thirds, thus addressing whether the potential differences can be considered clinically acceptable or not. Methods: Two ‘maxillofacial’ methods based on the trigeminal nerve distribution and one ‘orthodontic’ method based on reference horizontal planes were used to identify the facial thirds on 3D facial models of 80 Italian healthy adults to calculate the asymmetry of the face, and the upper, middle, and lower thirds of the face differently selected by each method. As a measure of asymmetry, the Root Mean Square value was calculated through a mirroring surface-based registration. Intra- and inter-operator reliability was verified for each method. Differences and interchangeability between the methods were tested, respectively, by two-way repeated measures ANOVA (Analysis of Variance) and Bland–Altman and Similarity Percentage model analysis. Additionally, the time required to perform each method was assessed. Results: All methods demonstrated excellent intra- and inter-operator reliability. While the ANOVA analysis found significant differences (p < 0.001) for the majority of facial Regions of Interest between each method, the Bland–Altman analysis revealed that the differences were clinically acceptable (<0.50 mm) for all facial regions between the trigeminal methods, and for the face and the upper third of the face between the orthodontic method, which was revealed to be faster, and the trigeminal ones. The additional similarity percentage model provided visual support for the complete interchangeability of the two trigeminal methods, as evidenced by the lower Coefficient of Variation value. Conclusions: There is no best method for assessing facial asymmetry that applies to all types of clinical settings, as we have shown that different methods may not be completely interchangeable. However, we suggest that the methods based on the trigeminal subdivision can be used interchangeably in contexts where the morpho-functional analysis of maxillofacial regions with different embryological origins is considered. Thus, the clinical setting imposes the choice of one method over another and, as we have pointed out, the consequent comparison of data with those obtained with methods whose interchangeability has been demonstrated.